Osmolality-Dependent Relocation of Penicillin-Binding Protein PBP2 to the Division Site in Caulobacter crescentus - Hocking, Jason (American Society for Microbiology, 2012)
The synthesis of the peptidoglycan cell wall is carefully regulated in time and space. In nature, this essential process occurs in cells that live in fluctuating environments. Here we show that the spatial distributions of specific cell wall proteins in Caulobacter crescentus are sensitive to small external osmotic upshifts. The penicillin-binding protein PBP2, which is commonly branded as an essential cell elongation-specific transpeptidase, switches its localization from a dispersed, patchy pattern to an accumulation at the FtsZ ring location in response to osmotic upshifts as low as 40 mosmol/kg. This osmolality-dependent relocation to the division apparatus is initiated within less than a minute, while restoration to the patchy localization pattern is dependent on cell growth and takes 1 to 2 generations. Cell wall morphogenetic protein RodA and penicillin-binding protein PBP1a also change their spatial distribution by accumulating at the division site in response to external osmotic upshifts. Consistent with its ecological distribution, C. crescentus displays a narrow range of osmotolerance, with an upper limit of 225 mosmol/kg in minimal medium. Collectively, our findings reveal an unsuspected level of environmental regulation of cell wall protein behavior that is likely linked to an ecological adaptation.